RELEVANSI INDUSTRI KONSTRUKSI DALAM PEMBELAJARAN AUTOCAD DI SMK PEMBANGUNAN SEBAGAI UPAYA PENINGKATAN TENAGA DRAFTER - Rifyal Ahmad Sunardi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Vocational education has a crucial role in preparing a competent, qualified and ready-to-use workforce to meet industry needs. One of the key skills in the construction industry is the ability to use design software such as AutoCAD. However, there is often a gap between the material taught in schools and industry demands. The aim of this research is to examine the relevance of the construction industry in learning AutoCAD at Development Vocational Schools with the aim of improving the quality of drafters who are ready to use in the job market. This research will explore the impact of integrating industrial practices in the vocational school education curriculum, as well as analyzing efforts to improve the quality of drafters through learning AutoCAD at Development Vocational Schools. The method used is Literature Review, with a focus on reviewing 4 journals that match the title of the article I wrote. Based on the results of the literature, the research sample consisted of deputy principals, heads of expertise programs, building engineering teachers, and training on the use of AutoCAD as well as introducing BIM concepts in AutoCAD to students.